The detection of the pregnancy in sheep by ultrasound - D. Ali Dinç; Mehmet Güler (Eurasian Journal of Veterinary Sciences)
Pregnancy diagnosis' was carried out on 43 Merino ewes by means of Doppler-mode ultrasound (Preg-tone) after 35, 60, 75, 90, 105 and 120 th days of AI.